2004
DOI: 10.1111/j.1467-8551.2004.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Attitudinal Correlates of Employee Satisfaction with an ESOP

Abstract: Venneman]A firm's adoption of an employee stock ownership plan (ESOP) has been hypothesized to increase employee productivity. Resulting employee productivity is hypothesized to improve firm profitability and thus ultimately improve stock performance. Most studies to date have tested potential relationships between the mere presence of an ESOP and changes in employee productivity and firm profitability. Few studies have attempted to identify the variables that are associated with employee satisfaction with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…Managers do not have enough authority to affect job security and xxi salaries in public hospitals; however, they could make effective efforts in other areas of motivation to improve employee morale. Several researchers have concluded that employee job satisfaction in health care organizations is shown to be correlated with age, gender, marital status, number of children, graduation level and work experience years (Al-Ahmadi, 2002;Aronson et al, 2003;Blegen, 1993;Bodur, 2002;Chu et al, 2003;Gangadhraiah et al, 1990;Gigantesco et al, 2003;Hespanhol et al, 1999;Lyons et al, 2003;Hallock et al, 2004). In this current study, variables such as employees' age, gender, work experience years, marital status and organizational position were seen as having significant effects on their job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Managers do not have enough authority to affect job security and xxi salaries in public hospitals; however, they could make effective efforts in other areas of motivation to improve employee morale. Several researchers have concluded that employee job satisfaction in health care organizations is shown to be correlated with age, gender, marital status, number of children, graduation level and work experience years (Al-Ahmadi, 2002;Aronson et al, 2003;Blegen, 1993;Bodur, 2002;Chu et al, 2003;Gangadhraiah et al, 1990;Gigantesco et al, 2003;Hespanhol et al, 1999;Lyons et al, 2003;Hallock et al, 2004). In this current study, variables such as employees' age, gender, work experience years, marital status and organizational position were seen as having significant effects on their job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…These predictions are rooted in expectancy theory, which implies that employee expectations and perceptions of the share ownership plan will influence their propensity to participate in it (as well as their judgement on its effectiveness and their satisfaction with it). A widely held view within the employee ownership literature has been that employee-owners seek more control of decision-making from their involvement in ownership, as indicated by the finding that satisfaction with ownership is correlated with perceptions of control (Hallock, Salazar and Venneman, 2004;Klein and Hall, 1988). By contrast, another strand of the literature emphasizes the role of financial orientations; in particular, French (1987) has argued that employees primarily seek personal profit rather than control from their participation in ownership.…”
mentioning
confidence: 99%
“…Also the result clearly shows that teachers' education degree, gender and field of education have influence on determining mangers' management styles. But in many studies have found that employee job satisfaction had correlated with age, gender, marital status, graduation level, and work experiences years (Hallock et al, 2004;Chu et al, 2003;Aronson et al, 2003;Lyons et al, 2003;, Al-Ahmadi, 2002;, Bodur, 2002 Teachers Job Satisfaction…”
Section: Discussionmentioning
confidence: 99%